The Inflationary Impact of Wage Indexation - Frank Heinemann (Center for Economic Studies and ifo Institute (CESifo), 2003)
It is an open question whether and how indexed wage contracts reduce welfare or raise average inflation. This paper analyzes the impact of indexed wage contracts on inflation and social welfare in a BarroGordon model with discretionary monetary policy by endogenizing social costs of indexation. Main results are: Wage indexation reduces the inflation bias but may raise the variance of inflation rates. In social optimum wages are fully indexed to the price level, but this requires optimal wage adjustments to productivity shocks. If wage adjustments to productivity are suboptimal, the second best solution calls for nonindexed wage contracts and a central banker with balanced aspiration levels of employment and real wages. In case of decentralized wage bargaining, a prohibition of wage indexation may improve welfare.
Keywords: 330; monetary policy; Phillips curve; wage bargaining; wage indexation